Book Review: Understanding Environmental Policy Processes: Cases from Africa - Godwell Nhamo (Environmental Association of Southern Africa, 2003)
Keeley, J., & Scoones, I. (2003). Understanding Environmental Policy Processes: Cases from Africa. London: Earthscan.